Human Milk as a Source of Methylmercury Exposure in Infants. - Grandjean, P (1994)
As methylmercury is excreted in human milk and infants are particularly susceptible to toxicity due to this compound, the purpose of this study was to evaluate the possible transfer of methylmercury to infants via breast-feeding. In a community with a high intake of seafood, 583 children from a birth cohort were followed. The duration of nursing was recorded, and hair samples were obtained for mercury analysis at approximately 12 months of age. The hair mercury concentrations increased with the length of the nursing period, and those nursed throughout the first year showed the highest geometric mean (9.0 nmol/g or 1.8 microg/g). Human milk therefore seems to be an important source of methylmercury exposure in infants. An increasing time interval from weaning to hair sample collection was not associated with any detectable decrease in mercury concentrations. A slow or absent elimination of methylmercury during the first year after birth could explain this finding. In certain fishing communities, infants nursed for long periods may be at increased risk of developing methylmercury toxicity.